Porcellanidae (Crustacea: Decapoda: Anomura) from New Caledonia and the Loyalty Islands - Osawa, Masayuki (Zootaxa, 2007)
Thirty-one species of the family Porcellanidae are reported on the basis of rich material recently collected from New Caledonia and the Loyalty Islands. They include two species of Aliaporcellana Nakasone & Miyake, 1971, one of Capilliporcellana Haig, 1978, two of Enosteoides Johnson, 1970, one of Heteropolyonyx Osawa, 2001, four of Lissoporcellana Haig, 1978, two of Pachycheles Stimpson, 1858, 11 species of Petrolisthes Stimpson, 1858, one of Pisidia Leach, 1820, six of Polyonyx Stimpson, 1858, and one of Porcellana Lamarck, 1801. Two species, one each of Lissoporcellana and Polyonyx, are new to science and are herein described and illustrated. Some records greatly extend the previously known distribution ranges of their species. A neotype is designated for Polyonyx biunguiculatus (Dana, 1852), of which the type specimen is apparently lost, in order to fix its identity. A key to all the Indo-West Pacific porcellanid genera is provided. For the genera recorded from New Caledonia and the Loyalty Islands, keys to species known from whole the Indo-West Pacific or presently from the islands are also given.